BIMBINGAN DAN PELATIHAN TENTANG PENGEMBANGAN KEPRIBADIAN DAN ETIKA PADA ANGGOTA PKK RW 01 KEL.JATIMULYO KEC.LOWOKWARU KOTA MALANG - Mahmudatul Himma; Diana Eka P; Lilies Nur A; Eko Boedhi S (Publisher UPT P2M Politeknik Negeri Malang, 2020)
This community service activity aims to provide guidance and training on the importance of personality development to the community, especially for women who are organized in social activities, especially the PKK group. In accordance with the aim of this organization is to provide intensive education on family and community welfare so that mothers are the first educators in their families and their children at home and the community in general.The methods used in this service activity are lectures and questions and answers, namely the delivery of material about personality traits and how to develop them. Apart from lectures, discussions and questions and answers were also held to provide opportunities for participants to understand more about the material presented.The result of this activity is that the participants gain insight and understanding (cognition) about the importance of ethics and how to develop themselves, especially in facing the development of life in this global era, so that they can apply an effective personality in everyday life and easily adapt to technological developments.